2015
DOI: 10.1016/j.jmb.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between E. coli DnaK, ClpB and GrpE during Protein Disaggregation

Abstract: The DnaK/Hsp70 chaperone system and ClpB/Hsp104 collaboratively disaggregate protein aggregates and reactivate inactive proteins. The teamwork is specific: E. coli DnaK interacts with E. coli ClpB and yeast Hsp70, Ssa1, interacts with yeast Hsp104. This interaction is between the M-domains of hexameric ClpB/Hsp104 and the DnaK/Hsp70 nucleotide-binding domain (NBD). To identify the site on E. coli DnaK that interacts with ClpB, we substituted amino acid residues throughout the DnaK NBD. We found that several va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 64 publications
(126 reference statements)
4
60
0
1
Order By: Relevance
“…Through its cochaperone, DnaJ, DnaK initially binds to the aggregates, leading to the exposure of peptide segments that can be recognized by ClpB (5,6). DnaK then recruits ClpB to the site of aggregation through direct physical interaction (7,8), transferring the aggregate to ClpB. Using the energy derived from ATP hydrolysis, ClpB unravels the aggregate by threading single polypeptide chains, one at a time, through the central pore of its hexameric ring (9).…”
mentioning
confidence: 99%
“…Through its cochaperone, DnaJ, DnaK initially binds to the aggregates, leading to the exposure of peptide segments that can be recognized by ClpB (5,6). DnaK then recruits ClpB to the site of aggregation through direct physical interaction (7,8), transferring the aggregate to ClpB. Using the energy derived from ATP hydrolysis, ClpB unravels the aggregate by threading single polypeptide chains, one at a time, through the central pore of its hexameric ring (9).…”
mentioning
confidence: 99%
“…This interaction might facilitate substrate transfer between both chaperones, taking advantage of the opposite affinities for substrate proteins of their ADP and ATP states. This does not rule out the possibility that the DnaK NBD could also interact with ClpB, as seen by NMR for the Thermus homologues and by a recent mutagenesis study showing that DnaK variants with substitutions in subdomains IB and IIB were defective in ClpB interaction [69,90]. However, the interaction of ClpB with DnaK NBD did not significantly alter the ATPase activity and dynamics of ClpB, as found for the Hsp70 NBD domain that bound the M domain of Hsp104 without activating the disaggregase [68].…”
Section: Clpb Dynamics and Disaggregase Activitymentioning
confidence: 97%
“…GrpE and ClpB compete for binding to the NBD of DnaK in the absence of crowders [15,16]. Our previous study showed that crowding shifted the association equilibrium of ClpB toward the functional hexamer and favored a compact, ATP-like state of the disaggregase with higher affinity for DnaK, which resulted in an increased reactivation efficiency of the bichaperone complex [17].…”
Section: Crowding Allows Competition Of Clpb With Grpe For Dnak Bindingmentioning
confidence: 98%
“…When the aggregates are formed by extensively denatured proteins in which the unfolded proteins are enriched in intermolecular ÎČ-structure, their reactivation requires the concerted action of the DnaK system and the hexameric disaggregase ClpB (Hsp100). The ability of the DnaK system to work independently or associate with ClpB has been proposed to be controlled by the competition between GrpE and ClpB to bind the NBD of DnaK [15,16]. We have recently characterized the effect of macromolecular crowding on the association properties and activity of ClpB and on its interaction with the DnaK system to form the bichaperone complex [17].…”
Section: Introductionmentioning
confidence: 99%